Applications of Geographic Information Systems (GIS) in Supply Chain Management: Systematic Literature Review - Anastasia Tsakiridi (International Journal of Supply Chain Management, 2021)
To date, the knowledge regarding the potential uses of Geographic Information Systems (GIS) in Supply Chain Management (SCM) and how the GIS applications can deliver business benefits is limited. To explore the current uses of GIS in SCM, a systematic literature review (SLR) was conducted. Three databases (Web of Science, ProQuest and Business Source Premier) were explored, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. There were 79 papers included in the literature review. The combined findings showed that the GIS applications in SCM were a) network/ transportation analysis/ routing algorithms (53 papers), b) Location-Allocation Site Search/ Selection (using multiple-criteria decision analysis [MCDA]) (45 papers), c) spatial analysis (people or land) (34 papers), d) connection with optimisation tools (32 papers) and e) visualisation/ monitoring or Building Information Modelling (BIM) (8 papers). The industries and related Supply Chain (SC) domains that used GIS were a) Biomass Biofuel/Wood (33), b) Logistics (22), c) Humanitarian/ Emergency/ Healthcare (10), d) Food/ Agro-Industry (5), e) Petroleum/ Coal/ Shale Gas (3), f) Faecal Sludge (2), g) Recycle product footprint (2) and h) Construction (2). Moreover, the research case studies took place in 26 countries, and the most prominent GIS software provider was Esri’s ArcGIS. The findings suggested that GIS can significantly contribute to SCM decision making by providing answers to cost minimisation, supplier selection, facility location, SC network configuration and asset management.